The expansion of wheat thermal suitability of Russia in response to climate change. (November 2018) - Di Paola, A.; Caporaso, L.; Di Paola, F.; Bombelli, A.; Vasenev, I.; Nesterova, O.V.; Castaldi, S.; Valentini, R.
Abstract: The emergence of Russia as a major grain exporter is not only crucial for the world commercial agriculture and food security, but also for the country's economy. Here we examine the past-to-future thermal suitability for winter wheat ( Triticum aestivum, L. 1753) cultivation over Russia and compare it with the recent trends of wheat yields and harvested area. The analyses use a multi-model ensemble median of the most updated bias-corrected outputs from five CMIP5 Earth System Models (1950–2099) under two representative concentration pathways (RCP 4.5 and RCP 8.5) and the Era-Interim dataset (1979–2016). Our results show that the thermal suitability has increased by ∼10 Mha per decade since 1980. Consistently, winter wheat yields and harvested area have also increased over the last decade by ∼0.5 t/ha and ∼4 Mha, respectively. Moreover, a potential for the Russian wheat sector may still be exploited if we consider the abandoned land (∼27 Mha) after the collapse of the Soviet Union. Our results also show that the increase in heat availability and the reduction of the frost constraint will likely move the thermal suitability toward the north-western and the Far East regions. Conversely, increases of extreme heat events are projected in the southern regions of Russia, which currently represent the most productive and intensively managed wheat cultivation area. Our findings imply both opportunities and risks for the Russian wheat sector that calls for sustainable and farsighted land management strategies to comprehensively face the consequences of global warming.